Concentration, working speed and memory: Cognitive problems in young childhood cancer survivors and their siblings. Issue 5 (2nd February 2015) - Wengenroth, L.; Rueegg, C. S.; Michel, G.; Gianinazzi, M. E.; Essig, S.; von der Weid, N. X.; Grotzer, M.; Kuehni, Claudia E.; ,
Abstract : Background: Cognitive problems can have a negative effect on a person's education, but little is known about cognitive problems in young childhood cancer survivors (survivors). This study compared cognitive problems between survivors and their siblings, determined if cognitive problems decreased during recent treatment periods and identified characteristics associated with the presence of a cognitive problem in survivors. Methods: As part of the Swiss Childhood Cancer Survivor Study, a questionnaire was sent to all survivors, aged 8–20 years, registered in the Swiss Childhood Cancer Registry, diagnosed at age <16 years, who had survived ≥5 years. Parent‐reported (aged 8–15 years) and self‐reported (aged 16–20 years) cognitive problems (concentration, working speed, memory) were compared between survivors and siblings. Multivariable logistic regression was used to identify characteristics associated with cognitive problems in survivors. Results: Data from 840 survivors and 247 siblings were analyzed. More often than their siblings, survivors reported problems with concentration (12% vs. 6%; P = 0.020), slow working speed (20% vs. 8%; P = 0.001) or memory (33% vs. 15%; P < 0.001). Survivors from all treatment periods were more likely to report a cognitive problem than were siblings. Survivors of CNS tumors (OR = 2.82 compared to leukemia survivors, P < 0.001) and those who had received cranial irradiation (OR = 2.10, P = 0.010) were most severely affected. Conclusion: Childhood cancer survivors, even those treated recently (2001–2005), remain at risk to develop cognitive problems, suggesting a need to improve therapies. Survivors with cognitive problems should be given the opportunity to enter special education programs. Pediatr Blood Cancer 2015;62:875–882. © 2015 Wiley Periodicals, Inc.